Moderasi Beragama dan Akulturasi Agama Budaya: Sebuah Dinamika Hidup Beragama di Tana Toraja: Sebuah Dinamika Hidup Beragama di Tana Toraja - Darius, Gayus; Safril, Safril (Melo: Jurnal Studi Agama-agama, 2024)
Abstract: Conflicts driven by religious backgrounds or those claiming to represent religion pose significant threats, especially in societies that are highly diverse in terms of culture, ethnicity, race, and religion. In the Toraja community, the acculturation of religion and culture, along with religious moderation, serve as two models of religious practice to address religious conflicts. This study employs a descriptive qualitative research method, focusing on the values developed through the approaches of religious moderation and religious-cultural acculturation. The findings of this research reveal that religious moderation can be integrated with local culture, particularly the value of "karapasan," which aligns with the concept of religious moderation focused on humanity and the public good. Meanwhile, the religious-cultural acculturation approach is more dominant in seeking universal values without relying solely on religion as the moral framework. The socio-cultural approach creates universal values that are acceptable to both Christian and Muslim communities. In this context, it is evident that religion is not in conflict with culture; rather, both can interact and form a dialogue to achieve religious harmony in life. Abstrak: Konflik yang dipicu oleh latar belakang keagamaan atau yang mengatasnamakan agama memang membawa ancaman yang cukup besar apalagi dalam masyarakat yang sangat majemuk. Majemuk dalam budaya, suku, ras maupun agama. Di dalam masyarakat Toraja, akulturasi agama budaya dan moderasi beragama menjadi dua model beragama untuk mengatasi terjadinya konflik keagamaan. Tulisan ini menggunakan metode penelitian kualitatif deskriptif dengan berfokus pada nilai-nilai yang dikembangkan dari pendekatan moderasi beragama dan akulturasi agam-budaya. Hasil dari penelitian ini memperlihatkan bahwa moderasi beragama dapat diintegrasikan dengan budaya lokal khususnya nilai karapasan yang sejalan dengan konsep moderasi beragama yang berfokus pada kemanusiaan dan kemaslahatan umum. Sedangkan pendekatan akulturasi agama-budaya lebih dominan dalam mencari nilai-nilai universal tanpa menggunakan agama sebagai satu-satunya sumber nilai moral. Pendekatan sosio-kultural menciptakan nilai-nilai yang universal yang dapat diterima baik di kalangan umat Kristen maupun umat Islam. Dalam hal ini dapat dilihat bahwa agama tidak bersifat bertentangan dengan budaya; sebaliknya, keduanya bisa saling berinteraksi dan membentuk dialog dalam mewujudkan harmonisasi hidup beragama.